Minimum Income Schemes indexation in EU-27 - Kateryna Bornukova; Chrysa Leventi; Alberto Mazzon; Andrea Papini; Fidel Picos (European Commission, Joint Research Centre (JRC), 2025)
This paper examines the effectiveness of Minimum Income Schemes (MIS) across EU-27 countries during the high inflation period of 2021-2024. Using microsimulation techniques, we analyse how well MIS parameters kept pace with inflation and assess their capacity to protect vulnerable households from monetary poverty. Our results suggest that countries with automatic indexation mechanisms demonstrate superior poverty outcomes with respect to those lacking formal indexation mechanisms or implementing insufficient adjustments. Moreover, in some countries MIS seem able to mitigate a large part of the increase in poverty rates, while in others they have a limited potential to do so, even with optimal indexation conditions. This work demonstrates that the interaction between indexation mechanisms and underlying design features, such as coverage, generosity and eligibility criteria, fundamentally shapes the schemes' distributional outcomes.
Keywords: 330